Impaired Endothelial Function in Hereditary Angioedema During the Symptom-Free Period - Firinu, Davide; Bassareo, Pier P.; Zedda, Angela M.; Barca, Maria P.; Crisafulli, Antonio; Mercuro, Giuseppe; Del Giacco, Stefano (Frontiers in Physiology, 2018)
INTRODUCTION: the presence of coronary endothelial dysfunction was previously shown in Hereditary Angioedema (HAE) patients. The aim of our study was to evaluate the effect of HAE on systemic endothelial function and whether there was a relationship among endothelial function, asymmetric dimethylarginine (ADMA) -which is a strong inhibitor of nitric oxide synthesis-, and disease severity scores. METHODS: twenty-four HAE patients (18 females, aged 47.9±2 years) without factors known to interfere with endothelial function were studied and compared with 24 healthy peers age- and gender-matched. Endothelial function was assessed by means of non-invasive finger plethysmography (reactive hyperaemia index: RHI) and ADMA levels by high-performance liquid chromatography. HAE severity scores have been calculated according to published literature. RESULTS: in HAE patients RHI was lower (2.03±0.46 vs 2.82 ± 0.34, p<0.0001) and ADMA higher (0.636±7 vs 585±5 micromol/L, p<0.01). than in controls. A statistically significant inverse correlation was revealed between RHI and patients’ ADMA levels (r=-0.516, p=0.009) as well as between RHI and patients’ chronological age (r=-0.49, p=0.015). A statistically significant correlation between RHI and ADMA was confirmed even when excluding the possible influence of cholesterol (r=−0.408, p=0.048). No other significant correlations were found with the examined laboratory and clinical parameters (chronological age, age at disease onset, disease duration, severity scores, and gender). CONCLUSION: the dysfunction previously shown in HAE patients at the coronary arteries seems to involve the peripheral vessels as well, without a correlation with disease severity.